Tamoxifen vs Tamoxifen plus 13-cis-retinoic acid vs Tamoxifen plus Interferon a–2a as first-line endocrine treatments in advanced breast cancer: updated results of a phase II, prospective, randomised multicentre trial - Dalla Chiesa, M.; Passalacqua, R.; Michiara, et al., M. (Acta Biomedica Atenei Parmensis, 2007)
Aims and background: To demonstrate the efficacy of 13-cis-retinoic acid (RA) or Interferon a-2a (IFN a-2a) with Tamoxifen (TAM) in the treatment of advanced breast cancer. Methods: Ninety-nine postmenopausal patients with advanced breast cancer, and a positive or unknown estrogen (ER) or progesterone (PgR) receptor status, were randomised to receive TAM 20 mg/m2/day orally (arm A), or TAM plus RA 1 mg/kg/day orally (arm B), or TAM plus IFN a-2a 3 MU thrice a week intramuscular (arm C). The three treatment groups were well balanced in terms of the main prognostic factors. Results: Response was evaluable in 32 of the patients in arm A, 32 in arm B, and 30 in arm C. Intention-to-treat analysis showed no significant difference of response rate in the three arms (44% vs 38% vs 42%). After an eight years median follow-up, there was no significant between-group difference in median overall survival: 47.4 vs 38.2 vs 45.1 months. Side effects were negligible in arm A, but cutaneous (39%) and mucosal (62%) toxicities were frequent in arm B, and flu-like syndrome and/or myalgia (46%) in arm C. Conclusions: The administration of RA or IFN a-2a does not add anything to the therapeutic effects of TAM.